The Correlation Between the Students’ Pronunciation Mastery and Their Ability in Speaking - Meylan GNA Sihombing (International Conference on Education and Language (ICEL), 2014)
Mostly students cannot speak fluently because they lack of pronunciation of how to pronounce the words correctly. They have difficulty in their conversation comprehending or understanding with someone they talk to because lack of the ability to pronounce the words. The objective of this research was to find out the correlation between the students’ pronunciation mastery and their ability in speaking of grade eight students of SMPN 21 Bandar Lampung. Two kinds of tests were administered. They were pronunciation test and speaking test. In the pronunciation test, spoken tests were used, each student was asked to read 50 item words and sentences in English. For speaking test, each student also was asked to read the text consist of two paragraphs.  The method of this research was the correlational research. Data were analyzed using r-Product Moment. The result of was 0.910. The p-value in 5% was 0.361 and in 1% was 0.463. So, the result showed that there was a significant correlation between the students’ pronunciation mastery and their ability in speaking of grade eight students of SMPN 12 Bandar Lampung. Based on the result of the research, it was important both for the English teachers and the students to realize one of the factors that gave positive contribution to the students’ ability in speaking was their pronunciation mastery